BIOMONITORING KUALITAS AIR SUNGAI MADIUN DENGAN BIOINDIKATOR MAKROINVERTEBRATA - Joko Widiyanto; Ani Sulistyarsi (IKIP PGRI MADIUN, 2016)
The objective of this research is to know the varieties of macro invertebrate species and water quality of the rivers in Madiun. The researcher used macro invertebrate as bio indicator. The result of the study can be used as references to the people to fulfill water need. This research used bio monitoring with macro invertebrate as bio indicator. The technique which was used in this research was purposes random sampling. The samples were taken from four differences places. They were taken from the upstream, the middle of the river, and the downstream. The samples were taken once in two weeks for two months. The researcher used Family Biotic Index (FBI) to analyze the data that was supported by physic and chemistry parameter. From the research that has been done in station 1, the researcher found one hundred and fifty species, FBI: 6, 58. It meant that the water quality was bad, with the highest pollution. In station 2, the researcher found two hundreds and seventy nine species, FBI: 6, 49, it meant that water quality was bad with the high pollution. In station 3, the researcher found three hundred and forty two species, FBI = 6, 64. It meant that the water quality was bad, with the high pollution. And in station 4, the researcher found fifty one species FBI=6, 58, meant that the water quality was bad with the high pollution. Based on the macro invertebrate samples that were found in above, the researcher found t13n families were resistant to pollution.